2020
DOI: 10.1101/2020.03.27.011064
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The forensic landscape and the population genetic analyses of Hainan Li based on massively parallel sequencing DNA profiling

Abstract: Due to the formation of the Qiongzhou Strait by climate change and marine transition, Hainan island isolated from the mainland southern China during the Last Glacial Maximum. Hainan island, located at the southernmost part of China and separated from the Leizhou Peninsula by the Qiongzhou Strait, laid on one of the modern human northward migration routes from Southeast Asia to East Asia. The Hlai-language speaking Li minority, the second largest population after Han Chinese in Hainan island, is the direct desc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 162 publications
2
2
0
Order By: Relevance
“…To discern the detailed relationship between the Ha Hlai and other language‐speaking populations with different language families, we performed a PCA which included 193 populations (Cadenas, Zhivotovsky, Cavalli‐Sforza, Underhill, & Herrera, 2008; Cai et al, 2011; Chennakrishnaiah et al, 2013; Deng et al, 2013; Fan et al, 2020; Fan, Wang, Chen, Long, et al, 2018; Fan, Zhang, et al, 2018; Gan et al, 2008; Gayden et al, 2007; Khurana et al, 2014; Kwon, Lee, Lee, Yang, & Shin, 2015; Li, Wen, et al, 2008; Regueiro, Cadenas, Gayden, Underhill, & Herrera, 2006; Rowold et al, 2016, 2019; Wells et al, 2001; Wen et al, 2004) from all over the world with eight language families, 11,197 individuals in total (dataset 1). The PC1, PC2, and PC3 of the total variances accounted for 13.97%, 10.83%, and 8.91%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To discern the detailed relationship between the Ha Hlai and other language‐speaking populations with different language families, we performed a PCA which included 193 populations (Cadenas, Zhivotovsky, Cavalli‐Sforza, Underhill, & Herrera, 2008; Cai et al, 2011; Chennakrishnaiah et al, 2013; Deng et al, 2013; Fan et al, 2020; Fan, Wang, Chen, Long, et al, 2018; Fan, Zhang, et al, 2018; Gan et al, 2008; Gayden et al, 2007; Khurana et al, 2014; Kwon, Lee, Lee, Yang, & Shin, 2015; Li, Wen, et al, 2008; Regueiro, Cadenas, Gayden, Underhill, & Herrera, 2006; Rowold et al, 2016, 2019; Wells et al, 2001; Wen et al, 2004) from all over the world with eight language families, 11,197 individuals in total (dataset 1). The PC1, PC2, and PC3 of the total variances accounted for 13.97%, 10.83%, and 8.91%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A disequilibrium in sequencing depth was clearly observed among the different kinds of genetic markers. These sequencing results were within the acceptable criteria defined by the manufacturer and approximately consistent with previous MPS-related studies (Churchill et al, 2017;Guo et al, 2017;Köcher et al, 2018;Hollard et al, 2019;Hussing et al, 2019;Fan et al, 2020). Specifically, partial genetic markers presenting the lowest sequencing depths in this study, such as DYS460, DXS10103, and rs1736442, were also reported to perform poorly in other studies (Almalki et al, 2017;Guo et al, 2017;Jäger et al, 2017;Silvia et al, 2017;Xavier and Parson, 2017;Hollard et al, 2019;Fan et al, 2020).…”
Section: Sequencing Performancesupporting
confidence: 91%
“…These sequencing results were within the acceptable criteria defined by the manufacturer and approximately consistent with previous MPS-related studies (Churchill et al, 2017;Guo et al, 2017;Köcher et al, 2018;Hollard et al, 2019;Hussing et al, 2019;Fan et al, 2020). Specifically, partial genetic markers presenting the lowest sequencing depths in this study, such as DYS460, DXS10103, and rs1736442, were also reported to perform poorly in other studies (Almalki et al, 2017;Guo et al, 2017;Jäger et al, 2017;Silvia et al, 2017;Xavier and Parson, 2017;Hollard et al, 2019;Fan et al, 2020). It was speculated that the constant low detection of these markers might be in relation to amplicon length, low (below recommendations) copy number input DNA, inaccurate library quantification, or overmultiplexing of samples (Guo et al, 2017).…”
Section: Sequencing Performancesupporting
confidence: 89%
See 1 more Smart Citation